Social Work with Environmental Migrants: Exploring the Scope for Spiritually Sensitive Practice. Issue 2 (16th April 2021) - Pandya, Samta
Abstract: This article reports a survey of social workers' ( N = 1, 204) views on the scope for spiritually sensitive practice with environmental migrants. Results indicated some variations in models, assessment methods, techniques, and intervention goals. Social workers from North America and South America, females, Christians, and Hindus working with environmentally forced migrants, and with higher scores on personal spirituality measures, favored the strengths perspective and model of salutogenesis, spiritual life maps, and spiritual competencies open dialogue as assessment methods; meditation and mindfulness as congruous techniques; and intervention goals as comprehensibility–manageability–meaningfulness and positive coping. Social workers from the Asia-Pacific and African regions, males, Muslims, and Buddhists working with environmental emergency and environmentally induced economic migrants, and with lower personal spirituality scores, preferred the biopsychosocial model and transpersonal spectrum models, spiritual genograms and spiritual history assessment; techniques such as guided visualization, journal keeping, physical disciplines, and active imagination; and goals of interventions such as happiness and forgiveness.